Kemasan (Packaging) di Higashi- Konoike, Osaka, Jepang - Yulriawan Dafri (EKSPRESI, 2009)
Packaging in Higashi - Konoike, Osaka, Jepan. Packaging is a very important strategy to glamorize a product in order to attract the consumers attention. Sometimes packaging is so important that is cost more than the product itself in order to lure the consumer to buy it. Most consumer judge a product by its packaging before buying. It is logical to say that attractive packaging is crucial to attract people to imagine and finally buy a product, beside the other important functions of packaging itself such as to protect, store and transport goods. Recently, packaging manufacture in Japan also support the environmental issue like global warming with producing an ecojriendly products using a reuse, reduce and recycle material. Keywords: Packaging, Japan, product.